Skyscraper fire fighters
When a fire gets out of control in a skyscraper it tests fire fighters to their limits. Predicting how a fire is behaving high up in a building is almost impossible. The fire fighters who entered the Twin Towers on 11 September 2001 could only guess at what was happening almost 1000 feet above them. That fateful day brought about the death of 343 New York fire fighters. Fire investigator, Jose Torero, believes fire fighters need not be put in such danger and that new technology could have saved many of the 343 fire fighters who died doing their duty that day. He has spent the last ten years developing a system that could change the way fires are fought forever. It's called Firegrid. It's a revolutionary approach to fire fighting that could save thousands of lives.